Analysis of the Employment Profile Offered by Employers to Graduated Bachelors of “Public Health” In Medical Universities - Raushan Z Magsumova (Journal of Global Pharma Technology, 2018)
The purpose of this article was to improve the educational program for Bachelors of "Public Health" to prevent problems with their further employment. We have carried out an anonymous survey; we have also studied the curricula and employment lists of graduates. The research on the first three widespread vacancies for Public Health graduates in three medical universities has revealed the following positions: Epidemiologist, Statistics Specialist and Quality Assurance Manager. This should be taken into account in appropriate educational programs.Keywords: Employment analysis, Employment, Public Health graduates, Employment profile.